Could the Presence of Thrips AFFECT the Yield Potential of Genetically Modified and Conventional Maize? - Cagáň, Ľudovít; Bokor, Peter; Skoková Habuštová, Oxana (Toxins, 2022)
Maize pests like Ostrinia nubilalis and Diabrotica virgifera virgifera are eradicated using genetically modified maize. This study's goal was to see if the genetically modified maize MON810 is also toxic to thrips communities on maize. The impact of Bt maize on thrips diversity and abundance, as well as yield losses, was studied in the field in Borovce for three years (Slovakia). The study used 10 Bt and 10 non-Bt maize cultivars. Thrips were monitored every two weeks during the season using transparent sticky traps installed on the experimental plots (one per plot, 20 per year). In total, 3426 thrips were caught. Thrips populations usually peak around the end of July at BBCH55. Among the species identified were Limothrips denticornis, Limothrips cerealium, Haplothrips aculeatus, Frankliniella schultzei, Frankliniella occidentalis, Thrips tabaci, Aeolothrips fasciatus, Frankliniella tenuicornis, and Chirothrips spp. We found that MON810 maize had no effect on the occurrence or composition of thrips. Their presence was affected by the maize growth phase and growing seasons and partially by the weather. The direct effect on the grain yield was not confirmed. Our research contributed to scientific knowledge of thrips communities found on maize plants in Central Europe, including Bt maize.
Keywords: můry; brouci; Seasons; Thysanoptera; Animals; Zea mays; zvířata; Bt maize; geneticky modifikované rostliny; Coleoptera; Thripidae; roční období; Plants, Genetically Modified; pest control; abundance; non-target arthropods; Moths; kukuřice setá